Key to South American genera of Acanthocinini (Coleoptera, Cerambycidae, Lamiinae) with erect setae on elytral surface - Monné, Miguel A.; Santos-Silva, Antonio; Monné, Marcela L. (Zootaxa, 2020)
A key for identification of the 45 genera of Acanthocinini with erect setae on the elytra and which occur in South America is provided. A new synonymy is proposed for Trichonyssodrys Gilmour, 1957 (junior synonym of Pentheochaetes Melzer, 1932), resulting in new combinations for the following species: Pentheochaetes aureopilosa (Monné, 1990), P. cincta (Delfino, 1981), P. maculata (Gilmour, 1957), P. melasma (Delfino, 1981), and P. nessimiani (Monné & Monné, 2012). The gender of the species-group names in Pentheochaetes is corrected. Diagnosis for each genus is provided, as well as type-locality and geographical distribution of the type-species.